Investigación de propiedades de expectativas de futuros especialistas de perfil socionómico - Popovych, Ihor; Shcherbyna, Vitalii; Sultanova, Leila; Hulias, Inesa; Mamchur, Iryna (My University, 2021)
The article researches of social expectations’ properties of future specialists of socionomic profile. Psycholinguistic determinants of personality construction of social reality are established. It is emphasized that the variability of the requirements of the social space necessitates constant prognostic activity of the life’s subject. This practice is demonstrated in relation to natural object connections, in the sphere of processes of social interaction, social communication and speech construction in the form of peculiar social expectations. Relevant psychodiagnostic research tools were used: clear quantification of texts, created a coding matrix, carried out quantitative and qualitative content analysis, empirical distribution of all levels’ scales of the studied parameters, Spearman correlation was determined. The predominant properties of the respondents were established: internality (n=18; 51.43%); activity (n=20; 57.13%), moderate openness results (n=16; 45.71%). It is proved that the respondents, interpreting the social field, pay considerable attention to the reflexive aspects, take the position of “participant in the process”. It is shown how sign-semantic formations, acquiring subjective meanings, become an objective fact that affects the construction of social reality by the individual. An example of content-analytical measurement of human behavior is demonstrated.
Research of social expectations’ properties of future specialists of socionomic profile
Keywords: Internality; externality; ambivalence; polarity; types of expectations